2008
DOI: 10.1055/s-2008-1078738
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Suppresses Adiponectin Secretion by Adipocytes

Abstract: Obstructive sleep apnea (OSA), characterized by cyclic intermittent hypoxia (IH) during sleep, is an independent risk factor for cardiovascular disease. Adiponectin (APN), an adipocytokine secreted exclusively by adipocytes, possesses antiatherogenic properties. Low levels of APN, particularly the high-molecular-weight (HMW) form, are associated with an increased risk of cardiovascular disease. Here, we hypothesized that IH would result in the dysregulation of APN expression and secretion. 3T3-L1 adipocytes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 26 publications
(34 reference statements)
1
35
0
3
Order By: Relevance
“…Levels of APN are inversely correlated with the proportion of body fat in adults. 3T3-L1 adipocytes exposed to intermittent hypoxia for 48 h had a significant decrease in the secretion of total and high-molecular-weight APN compared with control adipocytes maintained in 21% O 2 under identical conditions [102]. NAKAGAWA et al [103] demonstrated lower levels of circulating APN in patients with severe OSAS and sustained hypoxia reduced APN concentrations in C57BL/6J mice and 3T3-L1 adipocytes.…”
Section: In Vitro/in Vivo Studiesmentioning
confidence: 99%
“…Levels of APN are inversely correlated with the proportion of body fat in adults. 3T3-L1 adipocytes exposed to intermittent hypoxia for 48 h had a significant decrease in the secretion of total and high-molecular-weight APN compared with control adipocytes maintained in 21% O 2 under identical conditions [102]. NAKAGAWA et al [103] demonstrated lower levels of circulating APN in patients with severe OSAS and sustained hypoxia reduced APN concentrations in C57BL/6J mice and 3T3-L1 adipocytes.…”
Section: In Vitro/in Vivo Studiesmentioning
confidence: 99%
“…It has been observed that sleep disruption and hypoxemia may produce alterations in the hypothalamic-pituitary-adrenal axis, which could be another factor in the causation of IR (41). Similarly, an increase in circulating free fatty acids (42) and a reduction in adiponectin secretion by adipocytes have been implicated (43).…”
Section: Original Articlementioning
confidence: 99%
“…47 However, other studies on leptin levels and OSA have shown no effect independent of adiposity. 85 Insulin resistance is associated with low levels of adiponectin, 86 although the mechanism remains unclear; intermittent hypoxia has been proposed as a putative mechanism so adiponectin concentrations have been studied in OSA, with equivocal findings. 55,83 Sleep duration/fragmented sleep.…”
Section: Compromised Metabolism Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%